Inactivating Mutations in CCDC141 Causing Idiopathic Hypogonadotrophic Hypogonadism/Kallmann Syndrome - Turan, Ihsan; Hutchins, B. Ian; Hacihamdioglu, Bulent; Ozbek, Mehmet Nuri; Kotan, Leman Damla; Ozkan, Yusuf; Topaloglu, Kemal (Karger, 2016)
[Abstract Not Available]